2023
DOI: 10.2147/idr.s410159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated in-vitro Exposure to Saudi Honey on Bacterial Resistance to Antibiotics and Biofilm Formation

Abdu Aldarhami,
Abdulrahman S Bazaid,
Husam Qanash
et al.

Abstract: Introduction:Although Sumra and Sidr Saudi honey is widely used in traditional medicine due to its potent activity, it is unknown whether its prolonged usage has impact upon bacterial virulence or leading to reduced antibiotic sensitivity. Thus, the study aims to investigate the effect of prolonged (repeated) in-vitro exposure to Saudi honey on the antibiotic susceptibility profiles and biofilm formation of pathogenic bacteria. Methods: Several bacteria, including Staphylococcus aureus, Escherichia coli, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Therefore, finding alternative treatments for biofilms is of great interest. Honey has been shown to have antibacterial properties, and recent studies have investigated its potential antibiofilm activity [ 29 ]. Antibiofilm activity refers to the ability of a substance to disrupt or prevent the formation of biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, finding alternative treatments for biofilms is of great interest. Honey has been shown to have antibacterial properties, and recent studies have investigated its potential antibiofilm activity [ 29 ]. Antibiofilm activity refers to the ability of a substance to disrupt or prevent the formation of biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Sidr honey is used to treat a wide variety of diseases across the globe, including liver disease, stomach ulcers, lung infections, malnutrition, digestion difficulties, constipation, eye infections, wound infections, and general health conditions. Bacteria can form a bacterial community called a biofilm which is resistant to antibiotics and thus considered a challenging global health problem [ 29 ]. Honey has shown activity to inhibit biofilm formation in pathogenic bacteria including Staphylococcus aureus [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its exclusivity, derived from the rare Sidr tree, contributes to its desirability. Its distinctive and robust taste, coupled with its potential medicinal properties, contributes to its popularity [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the field of natural compounds, Abdulrahman S. Bazaid et al identified, by GC-MS analysis, 2,4-dihydroxy-2,5-dimethyl-3(2 H )-furan-3-one and 1-methylcyclopropanemethanol as the major phytoconstituents of Sumra honey [ 1 ] and suggested that this source be used as a promising potential therapeutic tool against infections caused by MDR bacteria and fungi [ 2 ]. In addition, they proposed Sumra honey as a good candidate to inhibit bacterial cellular communication in strains of P. aeruginosa and C. violaceum [ 1 ].…”
mentioning
confidence: 99%